The awareness of effective financial planning among the students of Faculty of Business and Management UiTM Melaka City Campus / Mohd Sufian Ab Kadir … [et al.] - Ab Kadir, Mohd Sufian (2015)
Financial planning nowdays become important in routine personal life. The changes of world economic situation and cost of living and related to the changes policies by authorities bodies, give impact on financial planning because of limited sources of income. The awareness of financial planning among university students has become decreasing attention according to data and information of insolvency. The purpose of this study is to examine the personal knowledge, personal value, risk and return investment, and subjective to awareness of effective financial planning among university students. Data were collected from 200 respondents in Faculty of Business Management in UiTM Melaka City Campus. Conceptual framework has been designed for the research which the independent variables; personal knowledge, personal value and risk and return investment which affect the awareness of financial planning. Personal knowledge has the greatest effect on the awareness of financial planning among university students. Overall, the implication and recommendations for the future research also provided for the related of persons and authories bodies in Malaysia.